Analyzing the Relative Effectiveness of Professional Development Activities and Dimensions for Elementary School Teachers of English as a Foreign Language - Sheu, Ping-Huang (International Journal of Educational Studies, 2025)
This study employs correspondence analysis to examine how elementary school EFL teachers perceive the effectiveness of various professional development activities (PDA) in relation to key dimensions of teacher professional development (TPD). Data were collected from 139 in-service English teachers in Taiwanese elementary schools through a structured questionnaire. The analysis revealed that EFL teachers’ perceptions varied notably based on their years of teaching experience and academic qualifications. While professional growth, subject-specific development, and curriculum and teaching consistently emerged as core PD dimensions across groups, novice teachers and those with bachelor’s degrees tended to favor a wider array of collaborative and reflective activities, such as teaching journals, teacher communities, and portfolios. In contrast, more experienced and master’s-level teachers demonstrated a preference for integrated, content-focused approaches, particularly workshops and observation linked to classroom management. Across all subgroups, seminars and collaborative teaching showed weaker associations with perceived effectiveness, particularly when linked to abstract or less actionable PD dimensions. These findings highlight the importance of tailoring TPD programs to align with EFL teachers’ developmental stages and academic backgrounds. Differentiated, targeted TPD design may enhance both relevance and impact in supporting EFL teacher growth and instructional quality.